Routh Approximation: An Approach of Model Order Reduction in SISO and MIMO Systems - D. K. Sambariya; Omveer Sharma (Institute of Advanced Engineering and Science, 2016)
In this paper the Routh Approximation method is explored for getting the reduced order model of a higher order model. The reduced order modeling of a large system is necessary to ease the analysis of the system. The approach is examined and compared to single-input single-output (SISO) and multi-input multi-output (MIMO) systems. The response comparison is considered in terms of step response parameters and graphical comparisons. It is reported that the reduced order model using proposed Routh Approximation (RA) method is almost similar in behavior to that of with original systems.